Analysis of Cryptographic Utilization with Merkle-Damgård Algorithm - Nainggolan, Peronika Ulianti; Dennis Afrilyans Manik; Laurenzio Gratian A. Daeli; Flory E Bako (Login : Jurnal Teknologi Komputer, 2024)
Cryptography plays an important role in data security, especially in authentication and digital signatures. One method that is widely used in cryptographic hash functions is the Merkle-Damgård algorithm. This algorithm allows the transformation of variable-sized data into a fixed hash value through an iterative process with a compression function. This study aims to analyze and understand the working mechanism of the Merkle-Damgård algorithm and its implementation in a data security system. The methods used in this study include the hashing process by dividing messages into fixed blocks, adding padding, initializing the initial value, and iterating the compression function. Testing was carried out with the example of the plaintext "ABC" using a simple XOR operation. The results of the analysis show that the Merkle-Damgård algorithm can produce unique and deterministic hash values, making it effective in detecting data changes. However, this algorithm also has weaknesses against collision attacks, which is a challenge in its development. Therefore, a deep understanding of this algorithm is essential in improving the security of modern hash functions.